PENGARUH NPF TERHADAP LABA (ROA) DENGAN VARIABEL MODERATING BANK JABAR BANTEN SYARIAH TAHUN 2010-2023 - Resmawan, Haris; Hanifa Qolbi, Syifa (CV. Lafadz Jaya, 2025)
The main problem taken in this study is the high level of non-performing financing (NPF), which has a negative impact on profitability (ROA). Bank Jabar Banten Syariah (BJBS) during the period 2010-2023. This study aims to investigate the impact of NPF on ROA and the role of the capital adequacy ratio (CAR) as a moderating variable. The research method uses path analysis from the BJBS annual report that we have as secondary data. The search results prove that NPF has a significant negative impact on ROA with a path coefficient of -0.63 (p <0.001), which indicates that increasing non-performing financing substantially reduces bank profitability. However, CAR is not proven to moderate the relationship between NPF and ROA with a path coefficient of -0.27 (p = 0.12). The conclusion of this study confirms that financing risk management is more crucial than capital adequacy in maintaining BJBS profitability. This study suggests that banks improve the quality of the credit risk mitigation process, improve operational efficiency, and closely monitor non-performing financing. Further research can include other variables such as efficiency or risk management to provide a more comprehensive analysis.